Accuracy of self‐ and proxy‐rated hearing among older adults with and without cognitive impairment. Issue 2 (23rd November 2021) - Kim, Alexander S.; Betz, Joshua F.; Albert, Marilyn; Deal, Jennifer A.; Faucette, Sarah P.; Oh, Esther S.; Reed, Nicholas S.; Lin, Frank R.; Nieman, Carrie L.
Abstract: Background: Hearing loss is highly prevalent among older adults with cognitive impairment and may exacerbate neuropsychiatric symptoms and affect interactions with others. Although audiometry is the gold standard for measuring hearing, it is not always used in research or clinical settings focused on the care of individuals with cognitive impairment. Subjective assessments of hearing, both self‐ and proxy‐rated, are widespread but may not adequately capture the presence of hearing loss as compared to audiometry. This study investigates the concordance between subjective and objective hearing assessments among older adults with and without cognitive impairment and evaluates factors associated with concordance. Methods: Participants were a subset of the Atherosclerosis Risk in Communities Neurocognitive Study (ARIC‐NCS), a prospective cohort study representing four US communities with adjudicated cognitive diagnoses and audiometric data, totaling 3326 self‐rated and 520 proxy‐rated hearing assessments. Sensitivity and specificity were calculated, and multivariable logistic regression estimated the magnitude of the association between the concordance of hearing assessments and variables of interest. Results: Sensitivity and specificity for self‐rated hearing status were 71.2% and 85.9% among cognitively normal older adults, 61.1% and 84.9% among persons with MCI, and 52.6% and 81.2% among persons with dementia, respectively. For proxy‐rated hearing, sensitivity and specificity were 65.7% and 83.3% for persons with MCI and 73.3% and 60.3% for persons with dementia, respectively. Female sex was positively associated with concordance for self‐rated hearing assessments. Conclusions: The low sensitivity of self‐ and proxy‐rated hearing assessments compared to audiometry suggests that hearing loss among older adults with cognitive impairment may go underreported and unaddressed in subjective assessments. Clinicians and researchers should recognize the limitations of using self‐ and proxy‐rated hearing assessments as measures of hearing status and incorporate objective audiometric evaluation whenever possible. Abstract : See related editorial by Chodosh & Blustein in this issue.